Ghostnet impacts on globally threatened turtles, a spatial risk analysis for northern Australia. Issue 4 (10th January 2013) - Wilcox, C.; Hardesty, B.D.; Sharples, R.; Griffin, D.A.; Lawson, T.J.; Gunn, R.
Abstract As human population growth continues, so too does our waste, often with unintended consequences for wildlife. The estimated 640, 000 tons of fishing gear lost, abandoned, or discarded annually exerts a large but uncertain impact on marine species. These "ghostnets" drift in the ocean and can fish unattended for decades (ghost fishing), killing huge numbers of commercially valuable or threatened species. We developed an integrated analysis combining physical models of oceanic drift with ecological data on marine turtle species distribution and vulnerability to make quantitative predictions of threat. Using data from beach cleanups and fisheries in northern Australia, we assessed this biodiversity threat in an area where high densities of ghostnets encounter globally threatened turtles. Entanglement risk is well‐predicted by our model, as verified by independent strandings data. We identified a number of previously unknown high‐risk areas. We are also able to recommend efficient locations for surveillance and interception of abandoned fishing gear. Our work points the way forward for understanding the global threat from marine debris and making predictions that can guide regulation, enforcement, and conservation action.